Waiting For America : A Story of Emigration - Shrayer, Maxim, 1967- (UPCC book collections on Project Muse., 2012)
In 1987 a young Jewish man, the central figure in this book, leaves Moscow for good with his parents. They celebrate their freedom in Vienna and spend two months in Rome and the coastal resort of Ladispoli. While waiting in Europe for a U.S. refugee visa, the book's twenty-year-old poet quenches his thirst for sexual and cultural discovery. Through his colorful Austrian and Italian misadventures, he experiences the shock, thrill, and anonymity of being in a Western democracy, running into European roadblocks while shedding Soviet social taboos. As he anticipates entering a new life in America, he movingly describes the baggage that exiles bring with them, from the inescapable family ties to the sweet cargo of memory.